If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4y + -3)(7y + 6) = 0 Reorder the terms: (-3 + 4y)(7y + 6) = 0 Reorder the terms: (-3 + 4y)(6 + 7y) = 0 Multiply (-3 + 4y) * (6 + 7y) (-3(6 + 7y) + 4y * (6 + 7y)) = 0 ((6 * -3 + 7y * -3) + 4y * (6 + 7y)) = 0 ((-18 + -21y) + 4y * (6 + 7y)) = 0 (-18 + -21y + (6 * 4y + 7y * 4y)) = 0 (-18 + -21y + (24y + 28y2)) = 0 Combine like terms: -21y + 24y = 3y (-18 + 3y + 28y2) = 0 Solving -18 + 3y + 28y2 = 0 Solving for variable 'y'. Factor a trinomial. (-6 + -7y)(3 + -4y) = 0Subproblem 1
Set the factor '(-6 + -7y)' equal to zero and attempt to solve: Simplifying -6 + -7y = 0 Solving -6 + -7y = 0 Move all terms containing y to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -7y = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -7y = 0 + 6 -7y = 0 + 6 Combine like terms: 0 + 6 = 6 -7y = 6 Divide each side by '-7'. y = -0.8571428571 Simplifying y = -0.8571428571Subproblem 2
Set the factor '(3 + -4y)' equal to zero and attempt to solve: Simplifying 3 + -4y = 0 Solving 3 + -4y = 0 Move all terms containing y to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -4y = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -4y = 0 + -3 -4y = 0 + -3 Combine like terms: 0 + -3 = -3 -4y = -3 Divide each side by '-4'. y = 0.75 Simplifying y = 0.75Solution
y = {-0.8571428571, 0.75}
| 7m+5=21 | | 2y^2-8y=7 | | y/4+5=3(y-2) | | 0.10a+.011(a+3000)=1380 | | 3(2n+5)-3n=2(n+5)-3(2n-4) | | 3y^2-51y+90= | | 2d-3+3c-2d-3+3c=4d-12+6c | | -x-16=-5x | | y=-2.7x^2+30x+6.5 | | 93.96=4.7p+8.79p-2.6p | | 3(x+2)=9x+1-6x+5 | | -4(-5x-4)=-44 | | x-.3x=200 | | 5.1-x=20.3 | | .25(-8x+8)=-2+2x | | x^2-13x*y+40y^2=0 | | 2(7d-6)+8= | | lx+2l=-lx-2l | | 50-10(4-2)+6= | | 0.56x-0.86=11.35-2.74x | | -5x+12=-3x-6 | | .25(-8x-8x)=-2+2x | | 4(x+6)=3x-2 | | 5x+12=-3x-6 | | -7(x+4)-45=5-22 | | -14+x=x+29 | | 3y=3(6.68)-3 | | .25(-x+8)=-2+2x | | 12=5y-25 | | 7n+14=-2n+50 | | 8a+5c=3369 | | 6x-1-3=4 |